The Paradox of the Lupus Anticoagulant: History and Perspectives - Pengo, Vittorio; Bison, Elisa; Denas, Gentian; Jose, Seena Padayattil; Bracco, Alessia; Banzato, Alessandra (Seminars in Thrombosis and Hemostasis, 2014)
A unique coagulation inhibitor prolonging whole-blood clotting time was described more than 50 years ago in two patients with systemic lupus erythematosus (SLE). The immunoglobulin nature of the inhibitor and its interaction with antiphospholipid antibodies was later demonstrated and the term “lupus anticoagulant (LA)” was coined to describe this laboratory finding. It soon became apparent that LA was a misnomer as it is often found in plasma from patients with clinical conditions other than SLE and is associated with thromboembolic events that may occur in otherwise healthy individuals. Individuals with LA have circulating autoantibodies that inhibits blood coagulation. These are mostly of IgG or IgM class and mainly directed against a phospholipid (PL)-binding plasma protein, β2-glycoprotein I (β2GPI). The presence of β2GPI-dependent LA represents a well-recognized risk factor for venous and arterial thromboembolism, as well as pregnancy loss and morbidity. β2GPI-dependent LA in the presence of documented previous thromboembolism, or history of pregnancy loss/morbidity, identifies definite anti-PL syndrome. Laboratory diagnosis of LA is thus of particular importance, as it may assign patients with a common event (thrombosis) to a group with a high risk for recurrence, which is a prerequisite for long-term oral antithrombotic treatment.
Keywords: lupus anticoagulant; β2-glycoprotein I; phospholipids; syndrome; thrombosis; pregnancy